Penyuluhan Kesehatan Masyarakat Mengenai Corona Virus bagi Guru, Murid dan Orang Tua di SD dan SMP Santa Theresia Malalayang Manado - rampengan, Novie; Rampengan, Starry Homenta (Vivabio: Jurnal Pengabdian Multidisiplin, 2023)
Corona virus infection causes high morbidity and mortality, so that make limitation of public activity including online teaching and learning process. Since January 2022 with the high coverage of corona vaccinations and sloping of corona cases, face to face learning has been carried out in Indonesia with various rules such as teacher and education personnel must have been vaccinated at least 2 times, providing handwashing places, wearing masks, maintaining distance, children being picked up by parents and etc. So the purposes of this partnership is to increase the knowledge of the students, parents and teachers about the corona protocol in schools and what to do if someone is infected with corona, how to transmit corona, how to prevent corona, implementation of 5M program, providing nutrition to prevent transmission and reduce number of illness and death due to corona. This service is carried out in the form of health counseling about corona, where a knowledge questionnaire about corona is filled out before and after the counseling. In filling out the questionnaire before the corona counseling, only 30% knowledge was obtained and the results increased to 90% after the corona counseling was carried out. In conclusion, health education about corona is needed to increase the knowledge of students, parents and teachers at Santa Theresia Malalayang Elementary and Middle School, Manado City.